Production of alkaline protease by Bacillus thuringiensis H 14 in aqueous two-phase systems - Hotha S.; Banik R.M. (My University, 2025)
Alkaline protease production by Bacillus thuringiensis H 14 was studied in aqueous two-phase systems composed of PEG X (X = 9000, 6000, 4000) and potassium phosphate. The top phase is continuous and rich in PEG while the bottom phase is dispersed and is rich in phosphate, microbial cells being mainly retained in the bottom phase. The alkaline protease produced during fermentation, partitioned into the upper phase (about 80%) and total protease produced were about 2.80 and 2.26 times higher than that of homogeneous fermentation when the fermentations were carried out in aqueous two-phase systems from the beginning and made after 45 h of inoculation respectively.; Alkaline protease production by Bacillus thuringiensis H 14 was studied in aqueous two-phase systems composed of PEG X (X = 9000, 6000, 4000) and potassium phosphate. The top phase is continuous and rich in PEG while the bottom phase is dispersed and is rich in phosphate, microbial cells being mainly retained in the bottom phase. The alkaline protease produced during fermentation, partitioned into the upper phase (about 80%) and total protease produced were about 2.80 and 2.26 times higher than that of homogeneous fermentation when the fermentations were carried out in aqueous two-phase systems from the beginning and made after 45 h of inoculation respectively.